User Interface Design Issues for Easy and Efficient Human Computer Interaction: An Explanatory Approach - Saha, Debasmita; Mandal, Ardhendu; Pal, SC (International Journal of Computer Sciences and Engineering, 2015)
User Interface (UI) is the part of the system that acts as an intermediately between the user and system facilitating the user to interact with the system in an efficient manner. The user interface is everything the end user comes into contact with while using the system physically, perceptually, and conceptually. To the end user, the user interface is the system itself. Hence, usability of a system remains one of the most important quality attribute in determining the total quality of any software system. The challenge of user-interface design is to construct a natural dialog sequence that allows the user and computer to exchange the messages required to carry out a particular task. The user interfaces do vary from system to system and user to user. In this paper we have identified the different issues in designing efficient user interface. All these issues are discussed at length with suitable example.